Compendium of statistics on bank group operations. - African Development Bank; African Development Bank.; African Development Bank. (Tunis, Tunisia : African Development Bank, Statistics Dept., 2007)
An annual publication of the African Development Bank Group, presenting data on operational activities of the Bank Group. Part one gives cross country statistics on Bank operations and part two provides country-specific information on each regional member country of the Bank.
oif 24/02/15
Ref.
Keywords: Development banks; Banks and banking